Analysis Of Bioactive Compounds From Sapindus Marginatus (Willd.) By Using Gas Chromatography-Mass Spectrometry Technique (Applied Biological Research, 2023)
This experiment was performed to detect the beneficial compounds present in  seed oil of Sapindus marginatus. The oil from the seeds of S. marginatus (Sapindaceae family) was extracted by the Soxhlet extraction technique using  petroleum ether as solvent at 60-800C. 22.18% oil was recovered from seeds  sample. The chemical compositions of seeds were examined by using GC-MS  technique. The GC-MS analysis showed that oil of S. marginatus contained more  than 40 compounds in total peaks area, out of which we discussed here mainly  six monounsaturated compounds according their retention time (RT) and  percentage of peak area, molecular formula and molecular weight. GC-MS  study revealed the presence of cis-vaccenic acid (C18:1), cis-13-octadecenoic acid  (C18:1) and trans-13-octadecenoic acid (C18:1) at RT 22.18 and its peak area was  40.48% of the compounds present in high amounts; whereas cis-13-eicosenoic  acid (C20:1), cis-11-eicosenoic acid (C20:1) and cis-10-nonadecenoic acid (C19:1) at  RT 23.56 and peak area 7.74 normally present in low amounts in seed oil, these  are prominent components in the seed oil.
Keywords: Fatty acids; GC-MS technique; Sapindaceae; Sapindus marginatus; seed oil